BOPP film for capacitor
By using a polypropylene composition with high content of propylene homopolymer and metal, the shortcomings in existing BOPP films in terms of crystallinity and heat resistance are solved, and improved capacitance characteristics and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411689167.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-27
- Filing Date
- 2021-05-21
- Publication Date
- 2025-02-11
AI Technical Summary
The existing BOPP films have shortcomings in improving crystallinity and heat resistance, which leads to poor performance in high temperature and mechanical properties, and are prone to serious defects such as membrane rupture.
Polypropylene compositions containing up to 100 wt% propylene homopolymer (A) with an isotactic five-unit portion content between 93.0% and 98.0% and a melt flow rate MFR2 of 0.4 g/ In the range of 10 min to 10.0 g/10 min, aluminum, titanium and other metals are added to the polypropylene composition to improve mechanical and electrical properties.
Improved capacitive characteristics such as durability and breakdown recovery are achieved, while improving the mechanical properties and heat resistance of the membrane, reducing the possibility of membrane rupture.
Smart Images

Figure BDA0005150443180000081 
Figure BDA0005150443180000171 
Figure BDA0005150443180000172
Abstract
Description
[0001] This application is a divisional application of the invention patent application with application number 202180037315.1, application date May 21, 2021, and invention name “BOPP film for capacitors”. Technical Field
[0002] The present invention relates to a novel BOPP film for capacitor film. Background Art
[0003] Polypropylene is used in many applications, for example, polypropylene is the preferred material in the field of film capacitors because its molecular chains lack any kind of polar groups that are oriented under electric field stress. Recently, inverters have been adopted in various types of electrical equipment, and with this trend, the demand for capacitors with smaller size and improved capacitance is also growing. Due to these market demands, biaxially oriented polypropylene (BOPP) films that are thinner and have improved mechanical and electrical properties are preferred for capacitor applications.
[0004] Capacitor films must withstand extreme conditions such as high temperatures and must have a high dielectric breakdown strength. In addition, it is more desirable that the capacitor film has good mechanical properties such as high hardness and high operating temperature. Up to 43% of the total capacitor film grades, i.e., power applications (such as welding, electric vehicles, trains, ovens, windmills, solar panels, etc.), use high isotactic polypropylene (HIPP) resins. In addition to balanced shrinkage and optimal surface roughness, the main advantage associated with high isotacticity is the high heat resistance of the final film, which is related to high crystallinity, high melting onset temperature and high peak melting temperature. Therefore, the latest attempts in this field are to improve the crystallinity and heat resistance of the material.
[0005] Furthermore, there is a particular need for polymers and films suitable for capacitor applications which have enhanced electrical properties, particularly with respect to breakdown resistance.
[0006] Description of the prior art:
[0007] EP 2701165 A1 and EP 2684676 A1 describe polypropylenes having a chain backbone with side branches, which are known to enhance the crystallization process of linear polypropylenes and are included in polypropylene resins to increase the melting temperature and heat resistance of the final BOPP film.
[0008] However, the increase in base resin crystallinity and melting point associated with the addition of branched polypropylene makes the material too hard, which usually reduces the toughness, i.e., elongation at break, of BOPP films made from such resins. This leads to serious defects in the BOPP production process, such as an increased likelihood of film rupture during BOPP production.
[0009] Therefore, there remains a need in the art to provide improved BOPP films for capacitors. Summary of the invention
[0010] Purpose of the invention
[0011] It is therefore an object of the present invention to provide such an improved membrane having improved capacitive properties, such as durability and / or breakdown resilience.
[0012] Accordingly, the present invention relates to a biaxially oriented polypropylene film comprising a polypropylene composition, wherein the polypropylene composition comprises a propylene homopolymer (A) having an isotactic pentad fraction content of 93.0 to 98.0%, a melt flow rate MFR2 according to ISO 1133 of 0.4 to 10.0 g / 10 min, an aluminum content of more than 0.0 ppm, a titanium content of more than 0.0 ppm and an ash content of more than 0.0 to 50.0 ppm, all based on the total amount of the polypropylene composition, characterized in that the ash contains from more than 0.0 wt% to at most 25.0 wt% of a metal selected from the group consisting of elements from IUPAC Group 4 to Group 13 inclusive of the Periodic Table of the Elements, based on the total amount of the ash content.
[0013] Viewed from another aspect, the present invention provides a process for producing the polypropylene contained in the polypropylene composition and the biaxially oriented polypropylene film.
[0014] Viewed from a further aspect the invention provides use of the polypropylene of the invention in a capacitor film or capacitor application.
[0015] The present invention also relates to a capacitor comprising an insulating film, wherein at least one layer of the film comprises the biaxially oriented polypropylene according to the present invention.
[0016] The present invention is described in more detail below. DETAILED DESCRIPTION
[0017] Detailed description:
[0018] The polypropylene composition according to the present invention may contain up to 100 wt% of propylene homopolymer (A). This is approximately the maximum reasonable content of component A, wherein the corresponding contents of the remaining components are still high enough to achieve the desired effect.
[0019] Accordingly, the preferred polypropylene composition of the present invention comprises 95.0-99.9 wt%, preferably 96.0-99.7 wt%, more preferably 97.0-99.5 wt%, e.g. 98.5-99.0 wt% of the polypropylene homopolymer (A).
[0020] The polypropylene composition may further comprise 0.01 wt% to equal to or lower than 1.0 wt% of conventional additives based on the total weight of the polypropylene composition. The additive may be selected from antioxidants, stabilizers, acid scavengers and mixtures thereof.
[0021] Typically, 1 ppm of additive corresponds to 1 mg of additive in 1 kg of polypropylene composition.
[0022] Preferably, the polypropylene composition consists of a propylene homopolymer (A).
[0023] It is contemplated that conventional additives may be present in the present invention even where "consisting of" language is used to define a composition in closed form.
[0024] The expression homopolymer as used in the present invention relates to a polypropylene which consists essentially, i.e. at least 99.5 wt.-%, more preferably at least 99.8 wt.-%, of propylene units. In a preferred embodiment only propylene units in the propylene homopolymer (H-PP) are detectable. The comonomer content can be determined by 13 C NMR spectroscopy was determined as described in the Examples below.
[0025] Furthermore, it is more desirable that the propylene homopolymer (A) is a linear polypropylene.
[0026] Furthermore, it is preferred that the propylene homopolymer (A) of the present invention has a melt flow rate (MFR) given in a specific range. The melt flow rate (ISO 1133) measured at 230°C under a load of 2.16 kg is denoted as MFR2 (230°C). Therefore, in the present invention, it is preferred that the polypropylene homopolymer (A) has an MFR2 (230°C) of at least 0.4 g / 10min, preferably at least 1.5 g / 10min, more preferably at least 2.5 g / 10min. Therefore, it is more desirable that the MFR2 (230°C) of the polypropylene homopolymer (A) measured according to ISO 1133 is in the range of 0.4 g / 10min to 10.0 g / 10min, preferably in the range of 1.5 g / 10min to 10.0 g / 10min, more preferably in the range of 2.5 g / 10min to 6.0 g / 10min, for example in the range of 2.5 g / 10min to 4.5 g / 10min.
[0027] An important feature of capacitor films is a low ash content, otherwise the dielectric properties are negatively affected. It is therefore more desirable that the ash content of the polypropylene homopolymer (A) and / or the composition and correspondingly in the biaxially oriented polypropylene film is rather low.
[0028] Accordingly, the polypropylene homopolymer (A) and / or the composition and the film may have an ash content of more than 0.0 ppm to 50.0 ppm, preferably in the range of 1.0 ppm - 40.0 ppm or in the range of 4.0 ppm - 30.0 ppm, like in the range of 7.0 ppm to 20 ppm.
[0029] To ensure sufficient dielectric breakdown field strength, the total amount of metal in the ash may be low.
[0030] Based on the total ash content, the total amount of metals in the ash (total) should be at most 25.0wt%, preferably in the range of greater than 0.0wt% to 25.0wt%, such as in the range of 1.0wt% to 20.0wt% or in the range of 3.0wt% to 15.0wt%.
[0031] In the context of the present invention, metals are understood to be elements selected from IUPAC Group 4 (titanium group) to and including Group 13. Preferably, the metal is an element selected from IUPAC Group 4 and / or Group 13.
[0032] In a preferred embodiment, the metal is aluminum and / or titanium. Preferably, aluminum and titanium are present simultaneously in the ash. In particular, aluminum and titanium are the only detectable metals in the ash.
[0033] In the present invention, neither calcium nor magnesium is considered to be a metal.
[0034] In a preferred embodiment, the total amount (combined) of aluminum and titanium in the ash may be up to 25.0 wt%, based on the total ash content, and may preferably be in the range of greater than 0.0 wt% to 25.0 wt%, such as in the range of 1.0 wt% to 20.0 wt% or in the range of 3.0 wt% to 15.0 wt%.
[0035] In one embodiment the polypropylene homopolymer (A) as well as the film may have an aluminum content between greater than 0.0 ppm and equal to or less than 1.50 ppm, such as between 0.30 ppm and equal to or less than 1.30 ppm, preferably between 0.50 ppm and equal to or less than 1.25 ppm.
[0036] Independently of the above, the propylene homopolymer (A) may have a titanium content ranging from equal to or more than 0 ppm to equal to or less than 1.00 ppm, preferably in the range of 0.20 ppm to equal to or less than 0.75 ppm, more preferably in the range of 0.30 ppm to equal to or less than 0.70 ppm.
[0037] The polypropylene and biaxially oriented polypropylene films of the present invention may have a specific weight ratio of aluminum content to titanium content. Ideally, the aluminum content is higher than the titanium content.
[0038] The weight ratio of aluminum to titanium may be in the range of 0.8-3.0, preferably 1.0-2.5 or 1.2-2.0.
[0039] In a preferred embodiment of the present invention, the polypropylene homopolymer (A) is highly isotactic. Therefore, it is more desirable that the polypropylene homopolymer (A) has a rather high pentad isotacticity. <mmmm>, i.e. higher than 93.0%, preferably higher than 96.0%. Preferably, the isotacticity of the polypropylene homopolymer (A) is <mmmm>In the range of 93.0% to 99.6%, more preferably in the range of 96.0% to 99.5%, and still more preferably in the range of 96.0% to 98.5%.
[0040] The melting temperature of the polypropylene homopolymer, composition and film may be at least 163.0°C, such as in the range of 163.0°C to 170.0°C, preferably in the range of 164.0°C to 168.0°C or in the range of 164.0°C to 166.0°C.
[0041] In another preferred embodiment of the present invention, the polypropylene homopolymer (A) of the present invention is characterized by a rather low xylene cold soluble (XCS) content, i.e. a xylene cold soluble (XCS) content of 2.0 wt% or less, more preferably 1.8 wt% or less, still more preferably 1.6 wt% or less. Therefore, it is more particularly desirable that the xylene cold soluble (XCS) content of the polypropylene homopolymer (A) of the present invention is in the range of 0.3 wt% to 2.0 wt%, more preferably 0.3 wt% to 1.8 wt%, more preferably 0.4 wt% to 1.6 wt%.
[0042] The xylene cold soluble (XCS) content also indicates that the polypropylene homopolymer (A) preferably does not contain any elastomeric polymer components, such as ethylene-propylene rubber. In other words, the polypropylene (PP) should not be a heterophasic polypropylene (i.e. a system consisting of a polypropylene matrix in which an elastomeric phase is dispersed). Such systems are characterized by a high xylene cold soluble content.
[0043] The polypropylene homopolymer used to prepare the biaxially oriented polypropylene film of the present invention can also be characterized by its decalin soluble fraction. The decalin soluble content of the polypropylene homopolymer can be in the range of 0.0 wt% to 3.5 wt%, such as in the range of 1.0 wt% to 3.0 wt% or in the range of 1.3 wt% to 2.5 wt%.
[0044] The biaxially oriented polypropylene (BOPP) film according to this invention may comprise at least 80.0 wt%, more preferably at least 90.0 wt% of the polypropylene composition defined in the present invention, yet more preferably consists of the polypropylene composition defined in the present invention.
[0045] Therefore, given that the biaxially oriented polypropylene film of the present invention is primarily formed from the propylene composition and the propylene homopolymer, respectively, it is understood within the scope of the present invention that the properties disclosed for the polymer and the composition also apply to the film, and vice versa.
[0046] Measurement of dielectric breakdown field strength (E) according to DIN IEC 60243-2 b 63.2) and evaluated according to the method described in detail in IEEE Transactions on Dielectrics and Electrical Insulation (2013), Vol. 20 (3), pp. 937-946. The dielectric breakdown field strength is obtained as the scale parameter α of a two-parameter Weibull distribution based on a fit of 50 results using a 250 V / s DC voltage ramp rate and a 2.84 cm 2 Measurement of active electrode area.
[0047] In one embodiment, the dielectric breakdown field strength Eb63.2 of the film can be 550 kJ / m 2 / mm to 630kJ / m 2 / mm, preferably between 570 kV / mm and 620 kV / mm, and preferably between 580 kV / mm and 610 kV / mm.
[0048] Furthermore, the biaxially oriented polypropylene (BOPP) film of the present invention can be used for capacitor films. In this case, the capacitor film comprises at least 80.0 wt%, more preferably at least 90.0 wt%, and still more preferably at least 99.0 wt% of the polypropylene composition or the biaxially oriented polypropylene (BOPP) film. In a particularly preferred embodiment, the capacitor film consists of the polypropylene composition or the biaxially oriented polypropylene (BOPP) film according to the present invention.
[0049] Preferably, the biaxially oriented polypropylene (BOPP) film may have a stretch ratio of at least 4 times, preferably at least 5 times in the machine direction, and a stretch ratio of at least 4 times, preferably at least 5 times in the transverse direction, more preferably, a stretch ratio of at least 9 times in the machine direction and a stretch ratio of at least 5 times in the transverse direction.
[0050] The film may be stretched in both the machine and transverse directions.
[0051] The capacitor film, i.e. the biaxially oriented polypropylene (BOPP) film, can be prepared by conventional stretching processes known in the art. Thus, the process for the manufacture of the capacitor film, i.e. the process for the manufacture of the biaxially oriented polypropylene (BO polypropylene) film, according to the present invention, comprises using the polypropylene composition defined herein, and forming the film thereof preferably by a tenter frame method known in the art.
[0052] The tenter process is a particular process in which the polypropylene composition defined herein is melt extruded from a slot die (e.g., a T-die) and cooled on a cooling drum to obtain an unstretched sheet. The sheet is preheated, for example, by a heated metal roll, and then stretched in the length direction between a plurality of rolls, on which different peripheral speeds are used, and then clamped at both edges with clips and stretched in the transverse direction in an oven by a tenter, thereby forming a biaxially stretched film. During longitudinal stretching, the temperature of the stretched sheet is preferably controlled within the temperature range of the melting point of the polypropylene defined herein (machine direction: -30°C to -10°C; transverse direction: -5°C to +10°C).
[0053] Subsequently, the capacitor film, i.e., biaxially oriented film (BOPP), can be subjected to corona discharge treatment in air, nitrogen, carbon dioxide gas, or any mixture on the surface to be metallized to improve the bonding strength with the metal to be deposited, and wound up by a winder.
[0054] The thickness of the biaxially oriented polypropylene film of the present invention may be in the range of 0.5 μm to 15.0 μm, preferably in the range of 1.0 μm to 10.0 μm or in the range of 3.0 μm to 8.0 μm.
[0055] In a preferred embodiment, the thickness of the biaxially oriented polypropylene film may be in the range of 1.0 μm to 5.0 μm, such as in the range of 2.0 μm to 4.0 μm.
[0056] In similar preferred embodiments, the biaxially oriented polypropylene film may have a thickness in the range of 3.0 μm to 10.0 μm, such as in the range of 4.0 μm to 8.0 μm or in the range of 5.0 μm to 7.0 μm.
[0057] In one embodiment, the film may comprise a layer consisting of the polypropylene composition. Optionally, the film may further comprise a metal layer.
[0058] The present invention also relates to a capacitor comprising an insulating film comprising a layer of a biaxially oriented polypropylene film according to the present invention, wherein the film may optionally comprise a metal layer.
[0059] The present invention also relates to a method for producing a biaxially oriented polypropylene film, comprising the following steps:
[0060] (1) Provide a polypropylene composition, comprising:
[0061] A propylene homopolymer (A) having an isotactic pentad fraction content of 93.0% to 98.0% and a melt flow rate MFR2 of 0.4 to 10.0 g / 10.0 min, and having:
[0062] an aluminum content greater than 0.0 ppm, optionally up to 1.50 ppm, and
[0063] A titanium content greater than 0.0 ppm, optionally up to 1.00 pppm, and
[0064] Ash content is 0.0ppm-50.0ppm,
[0065] All based on the total amount of the polypropylene composition,
[0066] Characterized in that, based on the total amount of the ash content, the ash contains greater than 0.0wt% to a maximum of 25.0wt%, preferably 1.0wt%-20.0wt% or 3.0wt%-15.0wt% of metals (in total) selected from the elements of IUPAC Group 4 to Group 13 (including Group 13) of the Periodic Table of the Elements, preferably aluminum and titanium,
[0067] (2) extruding the polypropylene composition into a flat film or sheet,
[0068] (3) orienting the flat film simultaneously in the machine direction and the transverse direction to obtain a biaxially oriented polypropylene film, and
[0069] (4) recovering the biaxially oriented polypropylene film, the film optionally having a dielectric breakdown field strength Eb63.2 between 550 kV / mm and 630 kV / mm, obtained as a scale parameter α of a fitted two-parameter Weibull distribution based on 50 results using a 250 V / s DC voltage ramp rate and a 2.84 cm 2 The active electrode area is measured.
[0070] In one embodiment of the process the polypropylene composition further comprises equal to or greater than 99.0 wt% of a propylene homopolymer, based on the total weight of the polypropylene composition.
[0071] In another embodiment of the method, the polypropylene composition may further comprise 0.01 wt% to 1.0 wt% of additives, based on the total weight of the polypropylene composition.
[0072] In another embodiment of the process, simultaneous orientation of the flat film in machine and transverse directions to obtain a biaxially oriented polypropylene film is carried out in a continuous process.
[0073] In another embodiment of the process the biaxially oriented polypropylene film is a film according to the present invention.
[0074] Aggregation methods
[0075] The present invention also relates to a slurry polymerization process for preparing a polypropylene homopolymer (A) having a decalin soluble content in the range of 0.0 wt% to 3.5 wt%, preferably in the range of 1.0 wt% to 3.0 wt%, more preferably in the range of 1.3 wt% to 2.5 wt%., wherein the catalyst system comprises:
[0076] a) Ziegler-Natta catalyst
[0077] b) Organic aluminum co-catalyst
[0078] c) External electron donor represented by formula (I)
[0079]
[0080] in:
[0081] R1 and R2 are independently H or a C1-C3 saturated or unsaturated hydrocarbon group, optionally linked together to form one or more cyclic structures;
[0082] R3 and R4 are independently H or C1-C4 hydrocarbon groups, optionally linked together to form one or more cyclic structures;
[0083] R5 is H or C1-C 12 Hydrocarbon,
[0084] The prerequisite is that at least one free radical of R3-R5 is not hydrogen.
[0085] The polypropylene homopolymer (A) prepared in the process of the present invention can have a relatively high pentad isotacticity. <mmmm>, i.e. higher than 93.0%, preferably higher than 96.0%, or higher. Preferably, the isotacticity of the polypropylene homopolymer (A) is <mmmm>In the range of 93.0% to 99.6%, preferably in the range of 96.0% to 99.5%, more preferably in the range of 96.0% to 98.5%.
[0086] The polymerization process described in the present invention can be a single mode or multimode slurry polymerization process for the production of polypropylene.Usually, propylene (co)polymer is produced on a commercial scale with a multimode process configuration.This multimode polymerization process known in the art comprises at least two polymerization stages.It is best to operate the polymerization stage in cascade mode.In a preferred embodiment, the multimode polymerization configuration comprises at least three slurry reactors operated in cascade mode.
[0087] The polymerization in slurry can be carried out in an inert diluent, typically a hydrocarbon diluent, such as methane, ethane, propane, n-butane, isobutane, pentane, hexane, heptane, octane, dodecane, etc. or a mixture thereof. Preferably, the diluent is a high boiling hydrocarbon having 10 to 14 carbon atoms, such as dodecane or a mixture of such hydrocarbons. In propylene polymerization, the monomer is typically used as the reaction medium.
[0088] The temperature in the slurry polymerization is generally from 40 to 115° C., preferably from 60 to 110° C., in particular from 65 to 90° C. The pressure is from 1 to 150 bar, preferably from 5 to 80 bar.
[0089] Slurry polymerization can be carried out in any known reactor for slurry polymerization. Such reactors include continuous stirred tank reactors and loop reactors. It is particularly preferred to carry out polymerization in a stirred tank reactor. Optionally, as known in the art, hydrogen is fed into the reactor to control the molecular weight of the polymer. The actual amount of hydrogen feed depends on the desired melt index (or molecular weight) of the resulting polymer.
[0090] The catalyst system used in the present invention is based on a Ziegler-Natta catalyst comprising a Group 2 metal compound, a Group 4 to Group 10 transition metal compound, or a lanthanide or actinide compound, optionally a Group 13 metal compound and optionally an internal electron donor.
[0091] The Group 2 metal compound is preferably a magnesium compound, such as a magnesium halide, especially magnesium dichloride.
[0092] The transition metal compound is preferably a Group 4 to Group 6 compound, more preferably a Group 4 transition metal compound or a vanadium compound, and still more preferably a titanium compound. A particularly preferred titanium compound is of the formula X y Ti(OR 8 ) 4-y The halogen-containing titanium compound shown, wherein R 8 It is C 1-20 Alkyl, preferably C 2-10 Alkyl and more preferably C 2-8 alkyl, X is halogen, preferably chlorine, y is 1, 2, 3 or 4, preferably 3 or 4 and more preferably 4. Suitable titanium compounds include trialkoxytitanium monochloride, dialkoxy titanium dichloride, alkoxy titanium trichloride and titanium tetrachloride and titanium tetrachloride.
[0093] Even more preferably, the titanium compound is TiCl3.
[0094] As internal electron donors, if present in the catalyst, the following compounds are particularly suitable, carboxylic (di)acid (diesters), such as methacrylates, phthalates or non-phthalic carboxylic (di)acid (diesters), ethers, diethers or oxygen- or nitrogen-containing silicon compounds or mixtures thereof.
[0095] The polymerization process of the present invention comprises, in addition to the Ziegler-Natta catalyst defined above, a cocatalyst (also known as activator) and optionally an external electron donor. The cocatalyst and the external electron donor are supplied separately to the polymerization process, i.e. they are not part of the solid Ziegler-Natta catalyst.
[0096] The cocatalyst is an organometallic compound of a Group 13 metal, typically an aluminium compound. These compounds include alkyl aluminium and alkyl aluminium halides. Preferably, the alkyl is a C1-C8 alkyl, preferably a C1-C4 alkyl, and the halide is a chloride. Preferably, the cocatalyst is a tri(C1-C4)alkyl aluminium, a di(C1-C4)alkyl aluminium chloride or a (C1-C4)alkyl aluminium dichloride or a mixture thereof. Most preferably, the alkyl is an ethyl. In a specific embodiment, the cocatalyst is diethyl aluminium chloride (DEAC).
[0097] ad c) External electron donor:
[0098] In a preferred embodiment, each of R1, R2 and R3 may be independently H or methyl, and R4 and R5 may be independently selected from C1-C4 hydrocarbon groups, in particular C1-C2 hydrocarbon groups.
[0099] Alternatively, 2-ethylhexyl methacrylate (EHMA) or isobutyl methacrylate (iBMA) is preferably used as the external electron donor, and the latter is particularly preferred.
[0100] In one embodiment the propylene homopolymer (A) is obtainable by the above process (optionally obtained by the above process).
[0101] Accordingly, the biaxially oriented polypropylene film of the present invention comprises a polypropylene composition comprising the propylene homopolymer (A) obtainable by the above process (optionally obtained by the above process).
[0102] The present invention will now be described in further detail by way of the examples provided below:
[0103] Example:
[0104] Unless otherwise defined, the following term definitions and determination methods apply to the above general description as well as the following examples of the invention.
[0105] Measurement method
[0106] MFR2(230℃)
[0107] The melt flow rate MFR2 is measured according to ISO 1133 (230° C., 2.16 kg load).
[0108] Xylene cold soluble fraction (XCS wt%)
[0109] The xylene cold soluble fraction (XCS) is determined according to ISO 6427 at 23°C.
[0110] Decalin soluble fraction (DS)
[0111] 2 g of the polymer sample is dissolved in 100 ml of stabilized decalin (= decalin) by heating at 160°C and stirring for 1 hour. The solution is cooled at room temperature for 1 hour and then placed in a 25°C water bath for 1 hour. The solution is filtered. 20 ml of the filtrate is quantitatively transferred to an aluminum pan coated with tar. The pan is placed on a hot plate at 195°C and covered with a slow stream of nitrogen. When the residue in the pan is almost dry, the pan is placed in a vacuum oven at 140°C for 2 hours. The total solids concentration of the filtrate is a measure of the soluble portion.
[0112] Calculated decalin solubles = {(grams remaining) / (grams sample)} x 5 x 100%.
[0113] Differential Scanning Calorimetry (DSC)
[0114] Differential scanning calorimetry (DSC) analysis, melting temperature (T m ) and melting enthalpy (H m ), crystallization temperature (T c ) and heat of crystallization (H c , H CR ) was measured using a TA Instruments Q200 Differential Scanning Calorimeter (DSC) on 5 mg to 7 mg samples. The DSC was run in a hot / cold / hot cycle according to ISO11357 / Part 3 / Method C2 with a scan rate of 10°C / min over a temperature range of -30°C to +225°C. The crystallization temperature (T c ) and heat of crystallization (H c ) is determined by the cooling step, while the melting temperature (T m ) and melting enthalpy (H m ) is determined by the second heating step.
[0115] GPC
[0116] Average molecular weight (Mw, Mn) and molecular weight distribution (MWD), i.e. the ratio of Mw / Mn (where Mn is the number average molecular weight and Mw is the weight average molecular weight), were determined by gel permeation chromatography (GPC) according to ISO 16014-4:2003 and ASTM D 6474-99. A PolymerChar GPC instrument equipped with an infrared (IR) detector was used with 3x Olexis and 1xOlexis Guard columns from Polymer Laboratories and 1,2,4-trichlorobenzene (TCB, stabilized with 250 mg / L 2,6-di-tert-butyl-4-methylphenol) as solvent at 160°C and a constant flow rate of 1 mL / min. 200 μL of sample solution was injected for each analysis. The column set was calibrated using a universal calibration method with at least 15 narrow MWD polystyrene (PS) standards ranging from 0.5 kg / mol to 11500 kg / mol (according to ISO 16014-2:2003). Mark Houwink constants for PS, PE, and PP are as described in ASTM D 6474-99. All samples were prepared by dissolving 5.0 mg to 9.0 mg of polymer in 8 mL of stabilized TCB (same as mobile phase) (at 160°C) for 2.5 hours (for PP) or 3 hours (for PE) with continuous gentle shaking in the autosampler of the GPC instrument at up to 160°C.
[0117] Ash content:
[0118] The ash content of the polymer is determined gravimetrically by measuring the relative weight (parts per million) of the residue remaining after combustion of the original polymer.
[0119] The combustion residues were obtained by a two-step combustion process of the polymer samples in a platinum crucible.
[0120] The empty crucible was first heated to 1000 °C in a muffle furnace for 15 min and then cooled in a desiccator for 3 h.
[0121] The weight of the crucible was then determined on an analytical balance with a detection limit of 0.0001 g (result A).
[0122] 100 g of the polymer sample was then weighed into a crucible using an analytical balance with a detection limit of 0.0001 g (result B).
[0123] The crucible containing the sample is heated in a Bunsenburner flame to slowly oxidize the polymer into ash.
[0124] The crucible containing the ash was then heated to 1000°C for 15 minutes in a muffle furnace and then cooled in a desiccator for 3 hours.
[0125] The ash content was determined by weighing the crucible on an analytical balance with a detection limit of 0.0001 g (result C).
[0126] Ash content (ppm) is: [(CA) / B]*1000000, the weight of the residue divided by the weight of the polymer sample.
[0127] The above determinations of ash content were performed in duplicate and the average values were reported.
[0128] If the difference between the measured values is greater than 7 ppm, a third measurement is performed.
[0129] The metal content of the ash is understood as the total amount of metal residues related to the amount of ash.
[0130] Quantification of aluminum and titanium:
[0131] Titanium (Ti) and aluminum (Al) were determined from an acid extract of the residue by ICP-OES, inductively coupled plasma with emission spectroscopy (Optima 2000DV), and using acid standards. Ti and Al contents are reported in ppm. Preparation of acid extract: The residue was taken from 25 g of polymer and moistened with 10 ml of sulfuric acid-acetic acid mixture (10 ml of H2SO4 dissolved in 400 ml of acetic acid). The moistened sample was burned on a quartz disk by direct ignition. The residue obtained was then further heated in a muffle furnace at 625°C for 30 minutes. After cooling, the residue was dissolved in 20 ml of aqueous HCl (500 ml of HCl 37% / 500 demineralized water) and filtered through a Whatmann 41 filter. The liquid phase was diluted to 100 ml with demineralized water. The extract was analyzed by ICP-OES.
[0132] Quantitative microstructure by NMR spectroscopy
[0133] Quantitative nuclear magnetic resonance (NMR) spectroscopy was used to quantify the isotacticity and comonomer content of the polymers.
[0134] A Bruker Advance III 400 NMR spectrometer was used to analyze the ions at 400.15 MHz and 100.62 MHz in solution. 1 H and 13 C for quantitative 13 C{1H} NMR spectra were recorded using 13 All spectra were recorded with a C-optimized 10 mm extended temperature probe head at 125 °C using nitrogen for all pneumatic components.
[0135] For polypropylene homopolymer, about 200 mg of material was dissolved in 1,2-tetrachloroethane-d2 (TCE-d2). To ensure a homogeneous solution, the NMR tube was further heated in a rotary oven for at least 1 hour after initial sample preparation in a heater. After insertion of the magnet, the tube was rotated at 10 Hz. This setup is mainly used for the high resolution required for quantification of stereoregularity distribution (Busico, V., Cipullo, R., Prog. Polym. Sci. 26 (2001) 443; Busico, V.; Cipullo, R., Monaco, G., Vacatello, M., Segre, AL, Macromoleucles 30 (1997) 6251). A total of 8192 (8k) transients were obtained for each spectrum using NOE and a bi-level WALTZ16 decoupling scheme with standard single-pulse excitation (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D. Winniford, B., J. Mag. Reson. 187 (2007) 225; Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 11289).
[0136] For ethylene-propylene copolymers, about 200 mg of material was dissolved in 3 ml of 1,2-tetrachloroethane-d2 (TCE-d2) and chromium-(III)-acetylacetone (Cr(acac)3) to give a 65 mM solution of the relaxant in the solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 285 (2009), 475). To ensure a homogeneous solution, the NMR tube was further heated in a rotating oven for at least 1 hour after initial sample preparation in a heating block. After insertion of the magnet, the tube was rotated at 10 Hz. This setup was primarily used for high resolution and quantification required for accurate ethylene content quantification. Standard single pulse excitation was used without NOE, using an optimized tip cone angle, 1 s recycle delay, and a dual-level WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D. Winniford, B., J. Mag. Reson. 187 (2007) 225; Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 11289). A total of 6144 (6k) transients were obtained for each spectrum.
[0137] Processing, integration using a proprietary computer program 13 C{ 1 H} NMR quantitative spectrum and determine the relevant quantitative properties based on the integration.
[0138] For ethylene-propylene copolymers, all chemical shifts are indirectly referenced to the central methylene group of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. This approach allows analog reference even in the absence of this structural unit.
[0139] For polypropylene homopolymer, all chemical shifts were internally referenced to the methyl isotactic pentad (mmmm) at 21.85 ppm.
[0140] Characteristic signals corresponding to regio defects (Resconi, L., Cavallo, L., Fait, A., Piemontesi, F., Chem. Rev. 2000, 100, 1253; Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157; Cheng, HN, Macromolecules 17 (1984), 1950) or comonomers were observed.
[0141] The stereoregularity distribution is quantified by integrating the methyl region between 23.6 ppm and 19.7 ppm, correcting for any sites not associated with the stereo sequence of interest (Busico, V., Cipullo, R., Prog. Polym. Sci. 26 (2001) 443; Busico, V., Cipullo, R., Monaco, G., Vacatello, M., Segre, AL, Macromoleucles 30 (1997) 6251).
[0142] Specifically, the effects of regio defects and comonomers on the quantification of the tacticity distribution were corrected by subtracting representative regio defect and comonomer integrals from the specific integrated region of the stereo sequence.
[0143] Isotacticity is determined at the pentad level and is reported as the percentage of isotactic pentad (mmmm) sequences relative to all pentad sequences:
[0144] [mmmm]% = 100*(mmmm / sum of all pentads)
[0145] The method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) was used to obtain the 13 C{ 1 The ethylene mole fraction in the polymer is quantified by integrating the multiple signals over the entire spectral region of the 1H} spectrum. This method was chosen for its accuracy, robustness, and ability to account for the presence of regio defects when required. Minor adjustments to the integration region were made to increase applicability to a wider range of comonomer content.
[0146] The mole percentage of comonomer incorporated in the polymer was calculated from the mole fraction according to the following formula:
[0147] E[mol%]=100*fE
[0148] The weight percent of comonomer incorporated in the polymer was calculated from the mole fraction according to the following formula:
[0149] E[wt%]=100*(fE*28.05) / ((fE*28.05)+((1-fE)*42.08))
[0150] According to the method of Kakugo et al. (Kakugo, M., Naito, Y., Mizunuma, K., Miyatake, T. Macromolecules 15 (1982) 1150), the 13 C{ 1 The comonomer sequence distribution at the ternary level was determined by integrating the integral of multiple signals over the entire spectral area of the 1H} spectrum. This approach was chosen for its robustness. Minor adjustments to the integration area were made to increase applicability to a wider range of comonomer contents.
[0151] The mole percentage of a given comonomer terpolymer in a polymer is calculated from the mole fractions determined by the method of Kakugo et al. (Kakugo, M., Naito, Y., Mizunuma, K., Miyatake, T. Macromolecules 15 (1982) 1150) according to the following formula:
[0152] XXX[mol%]=100*fXXX
[0153] Dielectric breakdown strength
[0154] Breakdown test and electrode design:
[0155] The dielectric breakdown strength is determined in accordance with DIN IEC 60243-2 using direct current (DC), a voltage ramp rate of 250 V / s and a 2.84 cm 2 The active electrode area is given by the cylindrical electrode diameter (2.5 cm) minus 0.6 cm due to the edge radius of 0.3 cm (cylinder / electrode arrangement of IEC 60243-1 and -2).
[0156] The IEC 60243-2 standard electrode design is used with a modification of placing a BOPP film on the upper cylindrical electrode and a cushioning foam elastomer (like a mouse pad) wrapped with aluminum oxide foil placed on the ground electrode.
[0157] The dielectric breakdown field strength was evaluated according to the method described in detail in IEEE Transactions on Dielectrics and Electrical Insulation (2013), Vol. 20(3), pp. 937-946.
[0158] The dielectric breakdown field strength was obtained as the scale parameter α of a two-parameter Weibull distribution based on the fit of 50 results using a 250 V / s DC voltage ramp rate and a 2.84 cm 2 Measurement of active electrode area.
[0159] On each BOPP film, the breakdown strength was measured 50 times as described below. The 50 breakdown measurements were distributed over a range of about 2.5 m 2 The measurements were performed on a 10 × 5 grid on an area of BOPP film, i.e. 10 punctures in a row across the TD width and a total of 5 such rows were measured along the MD of the BOPP film.
[0160] To accomplish this measurement plan, BOPP film samples were cut from 50 grid locations and individually punctured according to the electrode design described above. The film side opposite the cold roll faced the upper electrode. Breakdowns outside the active electrode area by sparks were discarded. After a breakdown occurred, the film thickness was measured three times around the puncture hole and the average value was taken. The breakdown (electric field) intensity E b (kV / mm) is the breakdown voltage (kV) divided by the average specimen thickness d (mm).
[0161] Statistical evaluation
[0162] To evaluate the breakdown distribution, DBD, IEC 62539 recommends using extreme value distributions such as the two-parameter Weibull distribution (2-Weibull), the three-parameter Weibull distribution (3-Weibull), the lognormal distribution, and the first asymptotic extreme value distribution (1AEV). Typically, when the breakdown mechanism is unknown, the statistical distribution is chosen primarily by the quality of the fit. However, most authors use the Weibull distribution, where the cumulative density distribution function for a three-parameter variable is given by Equation 1:
[0163]
[0164] Equation 1: Cumulative density function of the Weibull distribution with three parameters α (scale), β (shape), and δ (location).
[0165]
[0166] Equation 2: Cumulative density function of the Weibull distribution with two parameters α (scale), β (shape).
[0167] Where F(E b ) is the breakdown field E b The cumulative failure probability at , α is the scale parameter representing the mean value of the distribution, β is the shape parameter representing the dispersion, and δ is the location parameter, which some people call the threshold parameter. When the application field is below the threshold, that is, for E b <δ, F(E b )=0, this form of Weibull distribution (3-Weibull) assumes that the failure probability is zero. This form of Weibull distribution is rarely used because most authors assume that δ=0, that is, failure can occur in any application (for E b >0,F(E b )>0 (Eq. 2). A two-parameter Weibull distribution is used here and the shape parameter α is reported as Eb63.2 as the (average) breakdown strength of the BOPP film. To obtain Eb63.2(α), a fitting procedure is required, i.e., varying the two parameters α and β so that the fitted Weibull distribution best matches the experimental data. This procedure can be performed as a general function of a plotting software such as Origin or a statistical software package such as Minitab.
[0168] Material Description:
[0169] Raw materials:
[0170] Methyl methacrylate, ethyl methacrylate, 2-ethylhexyl methacrylate, isobutyl methacrylate and tert-butyl methacrylate were supplied by Sigma Aldrich and were additionally sparged with argon before use as external electron donors in the polymerization. Diethylaluminum monochloride (DEAC) cocatalyst was supplied by Chemtura as a 10% solution in decane.
[0171] Lynx900 catalyst was supplied by Grace and used as received.
[0172] Polymerization conditions of the samples in Table 1:
[0173] The polymerization process was carried out using a parallel pressure reactor (PPR) according to the following protocol: The catalyst slurry in dodecane was preactivated overnight (~18 hours) by adding the targeted amount of aluminum activator (DEAC, as a solution in decane) and external electron donor (as a solution in decane). The slurry mixture was shaken and placed in a glove box overnight. The actual polymerization process started on the next day by evacuating and purging the reactor unit with gaseous propylene ten times. Then, solvent (decane) and scavenger (DEAC) were added to a total volume of 4.1 ml. The system was then pressurized to 40 psi (2.8 bar) with propylene in two stages. Then, hydrogen was added in the form of a H2 / N2 mixture in an appropriate ratio. After the addition of H2, the reactor was heated to 70°C and the temperature and pressure were stabilized. The preactivated catalyst slurry was homogenized on a stirring plate oscillating at 1500 rpm. Aliquots of the slurry were transferred to the unit one at a time using a robotic arm equipped with a needle. Additional decane was added as a chaser at the same time to bring the total liquid volume in the reactor to 5 ml. A needle wash step was performed after each catalyst addition. The additional solvent slightly reduced the pressure inside the unit; therefore, additional gas C3 was used to increase the pressure to 89 psi and maintained at this level throughout the polymerization. The polymerization lasted for 120 minutes and was then quenched by raising the pressure to 200 psi (13.8 bar) with CO2. The reactor was cooled and slowly ventilated and purged with nitrogen. All 48 vials were removed and transferred to a Genevac (a heated, evacuated centrifuge) where the solvent was evaporated overnight. The next day, the vials were weighed and compared to the original values to obtain the yield.
[0174] Inventive Embodiment IE1a-IBMA
[0175] Lynx900 catalyst was used for polymerization with isobutyl acrylate (iBMA) as external electron donor, the ratio of electron donor to Ti was 0.4 mol / mol, and the ratio of DEAC:Ti was 6 mol / mol.
[0176] The average catalytic activity of the 6 units was 0.27 g PP / mg cath and the Mw was 543000 g / mol. The collected polymer was characterized by a melting point of 165°C and an isotacticity of 96.49% mmmm for the NMR pentad. Thus, a combination of high Mw and isotacticity (C2) with high activity as in C1 was obtained using the electron donor of the present invention.
[0177] Example IE1a was produced on a laboratory scale, and Example IE1b of Table 2 was correspondingly produced on a larger scale.
[0178] Inventive Example IE2-EHMA
[0179] Lynx900 catalyst was polymerized with 2-ethylhexyl methacrylate (EHMA) as an external electron donor, the ratio of electron donor to Ti was 0.4 mol / mol, and DEAC:Ti was 6 mol / mol.
[0180] The average catalytic activity of the 6 units was 0.28 g PP / mg cath and the Mw was 553000 g / mol. The collected polymer was characterized by a melting point (Mp) of 164.8° C. Again, a combination of high Mw and isotacticity (C2) with high activity (C1) was obtained using the electron donor of the present invention.
[0181] Comparative Example C1
[0182] Lynx900 catalyst was polymerized in the absence of any external electron donor with a diethylaluminum chloride (DEAC):Ti ratio of 6 mol / mol.
[0183] The average catalytic activity of the six units was 0.20 g PP / g cath and the Mw was 403000. The collected polymer was characterized by a melting point (Mp) of 161° C. and an NMR pentad isotacticity of 92.73%.
[0184] Comparative Example C2a MMA
[0185] Lynx900 catalyst was used for polymerization with methyl methacrylate (MMA) as external electron donor, the ratio of electron donor to Ti was 0.4 mol / mol, and the ratio of DEAC:Ti was 6 mol / mol.
[0186] The average catalytic activity of the 6 units was 0.135 g PP / mg cath and the Mw was 507000 g / mol. The collected polymer was characterized by a melting point (Mp) of 164.1°C and an NMR pentad isotacticity of 96.77%.
[0187] Example CE2a was produced on a laboratory scale and Example CE2b of Table 2 was correspondingly produced on a larger scale.
[0188] Comparative Example C3 EMA
[0189] Lynx900 catalyst was used for polymerization with ethyl methacrylate (EMA) as external electron donor, the ratio of electron donor to Ti was 0.4 mol / mol, and the ratio of DEAC:Ti was 6 mol / mol.
[0190] The average catalytic activity of the 6 units was 0.177 g PP / mg cath and the Mw was 493000 g / mol. The collected polymer was characterized by a melting point (Mp) of 163.7° C. The polymer produced with EMA (as C3) showed a similar low activity / high Mw balance as the polymer produced with MMA (as C2).
[0191] Comparative Example C4 TBMA
[0192] Lynx900 catalyst uses highly sterically hindered tert-butyl methacrylate (TBMA) as an external electron donor for polymerization, with the ratio of electron donor to Ti being 0.4 mol / mol and the ratio of DEAC:Ti being 6 mol / mol.
[0193] The average catalytic activity of the 6 units was 0.34 g PP / mg cath and the Mw was 430000 g / mol. The collected polymer was characterized by a melting point (Mp) of 161.1° C. Thus, the results were similar to Example C1 without electron donor (which produced a low Mw and low isotacticity material).
[0194] Table 1 Polymer properties (laboratory scale)
[0195]
[0196]
[0197] As shown in IE1a and IE2, the process of the present invention provides higher yields and allows the production of polypropylene with high molecular weight (Mw), higher melting temperature combined with high isotacticity - as shown in Table 2 below - with less catalyst residue in the polymer due to the higher yield.
[0198] Table 2 Polymerization of materials used to produce membranes:
[0199] Comparative Resin Example CE2b was produced as described in Comparative Example CE2 of EP2543684A.
[0200] Inventive Examples IE1 and IE2 of the present invention have been produced according to the reference example, but using isobutyl methacrylate instead of MMA in the catalyst preparation.
[0201] Membrane preparation:
[0202] The polypropylene composition was extruded using a pilot scale biaxial orientation line owned and operated by Brückner Maschinenbau GmbH. The film was extruded at a rate of about 30 kg / h on a chill roll maintained at 90°C and extruded into a 180 μm thick sheet at a chill roll / film speed of 10 m / min. The film was fed into an MDO unit consisting of 12 rolls at 10 m / min, where the first six rolls were heated from 95°C to 130°C to preheat the film, the next two rolls were maintained at 140°C for stretching, and the last four rolls were maintained at 110°C to 124°C for annealing. The machine direction (MD) stretching step was completed between the 8th and 9th rolls, running the 9th to 12th rolls at 50 m / min to produce an MDO or MD stretched film. The MDO film was continuously fed into a tenter frame using 180°C-175°C for preheating, 175°C-165°C for stretching, and 165°C-170°C for relaxation. In the tenter operation, the MD clip-to-clip distance was constant and the MDO film was stretched only in the transverse direction (TD) in the bifurcated stretching zone of the tenter. The engineering stretch ratio for MD and TD was 5.0 times 9.0.
[0203] The thickness of the produced film was 3.9 + / - 0.1 μm.
[0204] Table 2 Polymer properties measured on large scale samples:
[0205]
[0206]
[0207] The results show that the polymer and the biaxially oriented polypropylene film have lower aluminum and titanium residues in the polymer and lower metal content in the ash, and provide better dielectric breakdown strength. The object of the present invention is achieved.< / mmmm> < / mmmm> < / mmmm> < / mmmm>
Claims
1. A biaxially oriented polypropylene film comprising a polypropylene composition, wherein: The polypropylene composition comprises a propylene homopolymer (A) having: The content of the isotactic pentad fraction is 93.0% to 99.6%, The melt flow rate MFR2 measured according to ISO 1133 is 0.4 g / 10 min to 10.0 g / 10 min, Aluminum content greater than 0.0 ppm, and Titanium content greater than 0.0 ppm, and Ash content greater than 0.0ppm to 50.0ppm, All based on the total amount of the polypropylene composition, Characterized in that, based on the total amount of the ash content, the ash contains greater than 0.0 wt% to at most 25.0 wt% of metals selected from the elements of IUPAC Group 4 to Group 13 (including Group 13) of the Periodic Table of Elements.
2. The biaxially oriented polypropylene film according to claim 1, wherein The metal is an element of Group 4 and / or Group 13, preferably aluminium and / or titanium, and is optionally present in the range of 1.0 wt% to 20.0 wt% or 3.0 wt% to 15.0 wt% (total), based on the total ash content.
3. The biaxially oriented polypropylene film according to claim 1 or 2, wherein: The polypropylene has an aluminum content between greater than 0.0 ppm and 1.50 ppm, preferably between 0.30 ppm and 1.30 ppm or between 0.50 ppm and 1.25 ppm, and / or a titanium content between 0.0 ppm and 1.00 ppm, preferably between 0.20 ppm and 0.75 ppm or between 0.30 ppm and 0.70 ppm.
4. The biaxially oriented polypropylene film according to any one of the preceding claims, wherein: The ratio of aluminum to titanium in the ash is in the range of 0.8-3.0, preferably in the range of 1.0-2.5 or 1.2-2.0; and / or The polypropylene composition has an ash content of 1.0 ppm to 40.0 ppm or 4.0 ppm to 30.0 ppm.
5. The biaxially oriented polypropylene film according to any one of the preceding claims, wherein: The polypropylene composition comprises 95.0 to 99.9 wt% of the propylene homopolymer (A), based on the total weight of the polypropylene composition; and / or the propylene homopolymer (A) has a pentad isotacticity of 96.0 to 98.5%.
6. The biaxially oriented polypropylene film according to any one of the preceding claims, wherein: The membrane comprises: A layer consisting of a polypropylene composition, optionally comprising: Metal layer; and / or The film is stretched simultaneously in the machine and transverse directions.
7. The biaxially oriented polypropylene film according to any of the preceding claims, having a dielectric breakdown field strength E measured according to DIN IEC 60243-2 and obtained as a scale parameter α of a fitted two-parameter Weibull distribution based on 50 results of between 550 kV / mm and 630 kV / mm, preferably between 570 kV / mm and 620 kV / mm, or between 580 kV / mm and 610 kV / mm. b 63.2, the 50 results were obtained on films with a thickness of 3.8 μm-4.2 μm using a DC voltage ramp rate of 250 V / s and a 2.84 cm 2 The active electrode area is measured.
8. A capacitor comprising an insulating film comprising a layer of a biaxially oriented polypropylene film according to any one of the preceding claims.
9. Polypropylene homopolymer has: The content of the isotactic pentad fraction is 93.0% to 99.6%, The melt flow rate MFR2 measured according to ISO 1133 is 0.4 g / 10 min to 10.0 g / 10 min, Aluminum content greater than 0.0 ppm, and Titanium content greater than 0.0 ppm, and Ash content is 0.0ppm to 50.0ppm, All based on the total amount of the polypropylene composition, It is characterized in that The ash contains metals selected from the elements of IUPAC Group 4 to Group 13 (including Group 13) of the Periodic Table of the Elements in an amount (total) of greater than 0.0 wt% to at most 25.0 wt%, preferably 1.0 wt%-20.0 wt% or 3.0 wt%-15.0 wt%, based on the total ash content, and the metals are preferably aluminum and titanium.
10. The polypropylene homopolymer according to claim 9, having: The aluminum content is between greater than 0.0 ppm and 1.50 ppm, preferably between 0.30 ppm and 1.30 ppm or between 0.50 ppm and 1.25 ppm, and / or The titanium content is between greater than 0.0 ppm and 1.00 ppm, preferably between 0.20 ppm and 0.75 ppm or between 0.30 ppm and 0.70 ppm and / or The ratio of aluminum to titanium in the ash is in the range of 0.8-3.0, preferably in the range of 1.0-2.5 or 1.2-2.
0.
11. A method for producing a biaxially oriented polypropylene film, comprising the steps of: (A) provides a polypropylene composition comprising: A propylene homopolymer (A) having an isotactic pentad fraction content of 93.0% to 98.0% and a melt flow rate MFR2 of 0.4 g / 10.0 min to 10.0 g / 10.0 min, and having: an aluminum content greater than 0.0 ppm, optionally up to 1.50 ppm, and a titanium content greater than 0.0 ppm, optionally up to 1.00 ppm, and Ash content is 0.0ppm-50.0ppm, All based on the total amount of the polypropylene composition, Characterized in that, based on the total amount of the ash content, the ash contains greater than 0.0wt% to 25.0wt%, preferably 1.0wt% to 20.0wt% or 3.0wt% to 15.0wt% of metals (total) selected from the elements of IUPAC Group 4 to Group 13 (including Group 13) of the Periodic Table of the Elements, wherein the metals are preferably aluminum and titanium, (B) extruding the polypropylene composition into a flat film, (C) simultaneously orienting the flat film in the machine direction and the transverse direction to obtain a biaxially oriented polypropylene film, and (D) Recovering a biaxially oriented polypropylene film having a dielectric breakdown field strength Eb63.2 between 550 kV / mm and 630 kV / mm obtained as the scale parameter α of a fitted two-parameter Weibull distribution based on 50 results using a 250 V / s DC voltage ramp rate and a 2.84 cm 2 The active electrode area is measured.
12. The method according to claim 11, wherein: The polypropylene composition further comprises equal to or greater than 99.0 wt% of a propylene homopolymer and / or 0.01 wt% to equal to or less than 1.0 wt% of an additive, based on the total weight of the polypropylene composition.
13. The method according to any one of claims 11 or 12, wherein: Orienting the flat film simultaneously in the machine direction and in the transverse direction to obtain a biaxially oriented polypropylene film is carried out in a continuous process, and / or The biaxially oriented polypropylene film is a film according to any one of claims 1 to 9.
14. A slurry polymerization process for preparing a polypropylene homopolymer having a decalin soluble content between 0.0 wt% and 3.5 wt%, preferably between 1.0 wt% and 3.0 wt%, more preferably between 1.3 wt% and 2.5 wt%, wherein: The catalyst system includes: a) Ziegler-Natta catalyst, b) an organoaluminum co-catalyst, c) External electron donor of formula (I) in: R1 and R2 are independently H or a C1-C3 saturated or unsaturated hydrocarbon group, optionally linked together to form one or more cyclic structures; R3 and R4 are independently H or C1-C4 hydrocarbon groups, optionally linked together to form one or more cyclic structures; R5 is H or C1-C 12 Hydrocarbon, The prerequisite is that at least one free radical of R3-R5 is not hydrogen.
15. The polypropylene homopolymer according to claim 9 or 10 obtainable by the process according to claim 14.
Citation Information
Patent Citations
Process for the manufacture of isotactic polypropylene
EP2543684A1
Biaxially stretched polypropylene film, metallized film, and film capacitor
EP2684676A1
Biaxially stretched polypropylene film for capacitor, metallized film, and film capacitor
EP2701165A1